Developing a Teaching Practicum Model for ‘Krurakthin’ Scholarship Recipients in the Bachelor of Education Program, Kalasin University - Rittilun, Saksit; Puntaeak, Sukanda; Pattanachai, Nakintorn; Khansila, Paweena; Malasri, Amorn; Pimsak, Anucha (ASEAN Journal of Education, 2024)
This research aims to 1) investigate the current issues and challenges in the teaching practicum of early childhood education teachers and, 2) examine the components of the teaching practicum model for student teachers under the Teachers Return Home (henceforth Krurakthin) project at Kalasin University. The study targeted a group of 21 participants, including mentor teachers, school administrators, educational supervisors, representatives from destinations where schools were located, and faculty members specializing in early childhood education in the university network through purposive sampling. This research utilized focus group interview recording forms and an evaluation form to assess the appropriateness and feasibility of the training model. Data analysis involved calculating means, standard deviations, and content analysis. The research findings reveal challenges in the teaching practicum of early childhood education teachers within the Teachers Return Home (Krurakthin) project. Specifically, among student teachers, there are issues related to planning instructional activities, organizing experiences, classroom management, conducting classroom research, creating appropriate instructional materials, and assessing student outcomes. Mentor teachers exhibit a lack of understanding of their roles and inadequately demonstrate their responsibilities, coupled with a deficiency in collaborative efforts with instructional supervisors and educational institutions. School administrators lack a comprehensive understanding of their roles in guiding student teachers during their professional experience. In addition, instructional supervisors face challenges due to a lack of experience and skills in mentorship, and the execution of mentorship activities deviates from the planned guidelines. Some practicum schools chosen by students lack quality and fail to serve as exemplary institutions for student teachers. Furthermore, the teacher education institutions involved in the project exhibit inadequacies in their systems for supervising student teachers, with unclear assessment tools and criteria, and a deficiency in establishing understanding with the practicum schools. These identified challenges underscore the need for improvements in the overall structure and implementation of the teaching practicum model under the Krurakthin project. Additionally, the components of the training model for student teachers under the Teachers Return Home (Krurakthin) project at Kalasin University consist of five components: principles, objectives, operations, outcome assessment, and guidelines for successful implementation. The evaluation results indicated a high level of appropriateness (X̅=4.03, S.D.=0.68) and feasibility (X̅=4.02, S.D.=0.71) of the model.